Hubungan Kecerdasan Emosional terhadap Prestasi Belajar Siswa pada Mata Pelajaran IPS Kelas VIII di SMP Negeri 10 Kota Bengkulu - Lusi P Sari; Asiyah Asiyah; Salamah Salamah (UIN Fatmawati Sukarno Bengkulu, 2023)
This study aims to determine the relationship between emotional intelligence to student learning achievement I the class VIII social science subject at SMP Negeri 10 Bengkulu city. This study uses a type of quantitative method with a correlational approach to testing the relationship between two variables namely variable X and Y. The population of the study amounted to 191 students with a sample number of 66 students. Sampling techniques use random sampling techniques. Data collection techniques from this study are observation, questionnaires/ questionnaires, and documentation. Data analysis tecniques in the form of a prerequisite test, namely data normalit test, data homogeneity test, and data hypothesis. For normality tests using the Chi Squared formula (count), while the data hypothesis testing uses a comprelative product moment. Based on the results of the study it can be concluded that from the product moment corruption of ??? are 0,975. Then by viewing with the ?????? product moment coefficient of 66 is 0,975. Then it means greater than ?????? which is 0,975 ≥ 0,235. From this number showed a correlation between emotional intelligence to student learning achievement in the class VIII sosial science subject at SMP Negeri 10 Bengkulu city. Thus, for the alternative hypothesis (??) in the study was accepted, while the hypothesis of nihil (??) was rejected